Enriching the HSN With Individual Causes of Death. A Database for a Life-Course Analysis of Victims and Survivors - Tim Riswick (Historical Life Course Studies)
The focus of this article is on how a newly created database on causes of death in Amsterdam (1854–1940) may offer innovative insights by combining it with the available information from the Historical Sample of the Netherlands (HSN). By doing so, it illustrates how future research can help to provide new perspectives on ongoing debates on historical and contemporary infectious diseases by combining information from several historical sources and databases.